SMART SPECIALISATION AS A BASIC COMPONENT OF SOCIO-ECONOMIC DEVELOPMENT - Olena Guzenko; Svitlana Nikolaichuk; Dmytro Ivanenko (Baltic Journal of Economic Studies)
The European Union plays a pivotal role in supporting all regions and Member States to enhance their potential for innovation, competitiveness and sustainable development and growth. A primary instrument in the promotion of regional development is the implementation of the smart specialisation (SS) concept, which entails the identification of regional strengths and the cultivation of competitive advantages through the utilisation of the prevailing economic and innovation infrastructure. The analysis of the EU countries' experience has demonstrated that the SS concept fosters the establishment of an industrial and innovative foundation for the regional economy, delineates the distinctive characteristics of economic, scientific and technological specialisation among regions, and delineates the trajectories of their productivity, competitiveness and economic growth. In light of the crisis situation in the social and economic development of Ukraine's regions, the development and implementation of SS strategies at the regional level has the potential to enhance regional competitiveness, generate employment opportunities, and improve social conditions. Furthermore, the implementation of these strategies can also generate additional financial opportunities to support regional development. The subject of the present study is a set of theoretical and methodological aspects of innovative regional development through the implementation of the SS concept. The authors have set the task of formulating the main segments of the SS concept as a priority component of increasing the competitiveness of regions, improving their socio-economic climate and proposing a modernization of the conceptual category "SS of socio-economic development of regions" for a more substantive definition of the directions of innovative regional policy. The methodological basis of the study is based on the general principles of scientific knowledge: the principle of objectivity, which requires the identification of all the main obstacles to the implementation of the SS strategy in the regions; the principle of historicism, which provides for the coverage of the historical origins of the SS concept; the principle of a systematic approach, which allows to clarify the essence of the term "SS of the region"; the principle of logical generalisation, which contributes to the substantiation of the basic requirements for the successful implementation of the SS concept of the region and the definition of the key principles of SS implementation in the region. The study of such an innovative tool for regional development as SS has enabled the identification of several key segments of its essential content, which are taken into account by scientists and substantiated by the existing modern principles of its implementation. The authors analyse the individual stages of the emergence of the SS concept from the perspective of its historical formation, relevance and interconnection with the sustainable socio-economic growth of the region. This study pays particular attention to the main conceptual provisions of the SS concept. These include research and innovation strategies of SS, the choice of the region as the main object of specialisation, the use of scientific, technological and economic specialisation, and the attribution of key assets and the possible potential for diversification of the international position of the region as a local node in global chains to the main criteria for choosing subject areas. Simultaneously, the content of the primary barriers to the implementation of the SS strategy in the regions is delineated. These barriers are responsible for the slowdown in the promotion of innovation, industrial and socio-economic policy, and their further development. The principles of SS implementation in the region are outlined, with the establishment of the existing connection of their adaptation. The existence of a relationship between the SS concept and regional development, industrial and innovation policy is substantiated. Results. The SS concept of the regions is a priority tool for their competitiveness, social and economic development, taking into account production, innovation and economic potential. Achieving the strategic socio-economic intentions of regional development, ensuring the preservation of their specialisation and existing potential is impossible without the implementation of an effective SS Regions Concept. For Ukraine, the SS Regions concept represents the EU's assistance in promoting the development of Ukrainian regions and helping to overcome the prolonged economic downturn. It has been demonstrated that the benefits of this approach for Ukraine include the accession of regions to the EU network of regions, attracting investors to the region, increasing the number of joint projects with the EU, supporting regions in the process of economic transformation and aligning professional potential with market requirements. The authors of the study posit that the successful implementation of the concept of SS regions, the achievement of an appropriate level of competitiveness, and the improvement of socio-economic development can only be achieved through effective co-operation and synergy between local authorities, business, academia, and civil society.